Brand new P-doped g-C3N4: enhanced photocatalytic activity for H2 evolution and Rhodamine B degradation under visible light1. Issue 7 (21st February 2015) - Zhou, Yajun; Zhang, Lingxia; Liu, Jianjun; Fan, Xiangqian; Wang, Beizhou; Wang, Min; Ren, Wenchao; Wang, Jin; Li, Mengli; Shi, Jianlin
<x xml:space="preserve">Abstract</x> P-doped g-C3N4 has been successfully synthesized using hexachlorocyclotriphosphazene, a low cost and environmentally benign compound, as phosphorus source, and guanidiniumhydrochloride as g-C3N4 precursor, via a thermally induced copolymerization route.